Regulation of dietary polyphenols on cancer cell pyroptosis and the tumor immune microenvironment - Huang, Xiaoxia; Wang, Yao; Yang, Wenhui; Dong, Jing; Li, Lin (Frontiers in Nutrition, 2022)
Cancer is a major public health problem that threatens human life worldwide. In recent years, immunotherapy has made great progress in both clinical and laboratory research. But the high heterogeneity and dynamics of tumors makes immunotherapy not suitable for all cancers. Dietary polyphenols have attracted researchers’ attention due to their ability to induce cancer cell pyroptosis and to regulate the tumor immune microenvironment (TIME). This review expounds the regulation of dietary polyphenols and their new forms on cancer cell pyroptosis and the TIME. These dietary polyphenols include curcumin (CUR), resveratrol (RES), epigallocatechin gallate (EGCG), apigenin, triptolide (TPL), kaempferol, genistein and moscatilin. New forms of dietary polyphenols refer to their synthetic analogs and nano-delivery, liposomes. Studies in the past decade are included. The result shows that dietary polyphenols induce pyroptosis in breast cancer cells, liver cancer cells, oral squamous cells, carcinoma cells, and other cancer cells through different pathways. Moreover, dietary polyphenols exhibit great potential in the TIME regulation by modulating the programmed cell death protein 1(PD-1)/programmed death-ligand 1(PD-L1) axis, enhancing antitumor immune cells, weakening the function and activity of immunosuppressive cells, and targeting tumor-associated macrophages (TAMs) to reduce their tumor infiltration and promote their polarization toward the M1 type. Dietary polyphenols are also used with radiotherapy and chemotherapy to improve antitumor immunity and shape a beneficial TIME. In conclusion, dietary polyphenols induce cancer cell pyroptosis and regulate the TIME, providing new ideas for safer cancer cures.